2012
DOI: 10.1109/tpwrd.2011.2168428
|View full text |Cite
|
Sign up to set email alerts
|

Impact of VSC-Based Multiline FACTS Controllers on Distance Protection of Transmission Lines

Abstract: By utilizing multiline voltage-source (VSC)-based flexible ac transmission system (FACTS) controllers, independent controllability over each compensated line of a multiline system can be achieved. While VSC-based multiline FACTS controllers emerged as a new opportunity to control two independent ac systems, the main constraints and limitations that are presented to the conventional transmission-line protection systems need to be investigated. In this paper, the impacts of VSC-based FACTS controllers on distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…Impact of IPFC, UPFC and GUPFC were analyzed and found that measured impedance was higher than expected leading to false operation of relay. It was also found that GUPFC has the most severe influence than others with IPFC having the least impact [11].…”
Section: Facts Devicesmentioning
confidence: 90%
“…Impact of IPFC, UPFC and GUPFC were analyzed and found that measured impedance was higher than expected leading to false operation of relay. It was also found that GUPFC has the most severe influence than others with IPFC having the least impact [11].…”
Section: Facts Devicesmentioning
confidence: 90%
“…Majority of the studies have tackled these effects on impedance relays like the distance relays of transmission lines and loss-of-excitation (LOE) relays of synchronous generators, both of which are based on impedance measurements. Investigations in [1][2][3][4][5][6][7][8][9][10][11] analyze the distance relay performance in the presence of FACTS controllers. These studies can be categorized into three major parts based on different compensation devices: a) shunt-FACTS like static Var compensator (SVC) and static synchronous compensator (STATCOM) [1][2][3][4], b) series-FACTS like SSSC and thyristor controlled series capacitor (TCSC) [5][6][7], and c) shuntseries-FACTS like generalized interline power flow controller (GIPFC) and unified power flow controller (UPFC) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the researches have surveyed these effects on impedance relays such as the distance relays of transmission lines and loss-of-excitation (LOE) relays of synchronous generators, which both operate based on the impedance measurements. The distance relay performance is analyzed in [1][2][3][4][5][6][7][8][9][10][11] in the presence of FACTS controllers. These studies include three major investigation categories; which deal with; a) shunt-FACTS such as static Var compensator (SVC) and static synchronous compensator (STATCOM) [1][2][3][4], b) series-FACTS such as SSSC and thyristor controlled series capacitor (TCSC) [5][6][7], and c) shunt-series-FACTS such as unified powerflow controller (UPFC) and generalized interline powerflow controller (GIPFC) effects [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%